Soluble PD-L1 changes in advanced non-small cell lung cancer patients treated with PD-1 inhibitors: an individual patient data meta-analysis - Shimizu, Takashi; Inoue, Eisuke; Ohkuma, Ryotaro; Kobayashi, Shinichi; Tsunoda, Takuya; Wada, Satoshi (Frontiers in Immunology, 2023)
Introduction: Currently, first-line immune checkpoint inhibitors (ICIs), including programmed cell death protein-1 (PD-1) inhibitors, are utilized as monotherapy in advanced non-small cell lung cancer (NSCLC) patients with high programmed death ligand-1 (PD-L1) expression (≧50%). Pre-treatment or post-treatment serum soluble PD-L1 (sPD-L1) has been identified as a potential biomarker for assessing ICI efficacy through fixed-point observations. However, existing studies on sPD-L1 changes have produced inconsistent results or have had sample sizes too small to detect clinically meaningful effect sizes. To elucidate the role of sPD-L1, we conducted a collaborative individual patient data meta-analysis of PD-1 inhibitor treatments. Methods: We conducted a thorough search of articles in PubMed via Medline, Embase, Scopus, and Cochrane databases from inception to October 20, 2023. Trials were deemed eligible if they contained individual datasets for advanced NSCLC patients, including data on overall survival (OS) / progression-free survival (PFS), as well as pre- and post-treatment sPD-L1 levels after 3-4 cycles of PD-1 inhibitor treatments. Our analysis focused on patients who completed 3-4 cycles of PD-1 inhibitor treatments. The primary outcome measure was OS/PFS, and we assessed changes in sPD-L1 concentration pre- and post-treatment through ELISA analyses. Results: From our search, we identified a potential seven trials, encompassing 256 patients. Among these, two trials with 26 patients met the criteria for inclusion in our primary analyses. Over a median follow-up period of 10 months, pooled univariate analysis revealed that increases in sPD-L1 levels during PD-1 inhibitor treatment were not associated with OS (HR = 1.25; CI: 0.52–3.02)/PFS (HR = 1.42; CI: 0.61–3.30) when compared to cases with sPD-L1 decreases. Subgroup analyses indicated that the impact of sPD-L1 changes on overall mortality/ progression-related mortality remained consistent regardless of gender, age, or the type of treatment (nivolumab or pembrolizumab). Conclusions: Our findings suggest that changes in sPD-L1 levels during PD-1 inhibitor treatment do not significantly influence the prognosis of advanced NSCLC patients, regardless of gender, age, or treatment type. Continuous monitoring of sPD-L1 may not offer significant advantages compared to fixed-point observations.